2014
DOI: 10.1016/j.bbadis.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes under assault: Environmental disruption of adipose physiology

Abstract: The burgeoning obesity epidemic has placed enormous strains on individual and societal health mandating a careful search for pathogenic factors, including the contributions made by endocrine disrupting chemicals (EDCs). In addition to evidence that some exogenous chemicals have the capacity to modulate classical hormonal signaling axes, there is mounting evidence that several EDCs can also disrupt metabolic pathways and alter energy homeostasis. Adipose tissue appears to be a particularly important target of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 180 publications
(207 reference statements)
1
84
0
Order By: Relevance
“…Supporting these warnings are, among others, several epidemiological and in vivo studies that reported the positive correlation of EDCs concentrations, both in AT and plasma, with the prevalence of obesity, MetS, insulin resistance, hypertension and CVD 2123 , as well as adipocyte dysfunction 24 .…”
Section: Introductionmentioning
confidence: 83%
“…Supporting these warnings are, among others, several epidemiological and in vivo studies that reported the positive correlation of EDCs concentrations, both in AT and plasma, with the prevalence of obesity, MetS, insulin resistance, hypertension and CVD 2123 , as well as adipocyte dysfunction 24 .…”
Section: Introductionmentioning
confidence: 83%
“…Several mechanisms are plausible. EDCs have been shown to alter the differentiation of adipocytes [65, 66]. EDCs are capable of mediating changes in methylation patterns and regulate epigenetic encoding in cells, and epigenetic program control by such compounds are now well documented [6770].…”
Section: Endocrine Disrupting Chemicals (Pcbs Exposures) and Developmmentioning
confidence: 99%
“…Adipocytes producing normal levels of both leptin and adiponectin are thus essential for effective insulin signaling, and their dysfunction leads to disruption of insulin signaling (Mlinar and Marc, 2011). Adipocytes and fat tissue in general accumulate lipophilic toxicants such as PCBs and thus are likely to be affected by them (Regnier and Sargis, 2014). …”
Section: Introductionmentioning
confidence: 99%